(3eTJed GdCMcGes - (3aNQ GdOjf GdQhej,J (B879 (3g` s
(3ChdgG (B:s
(3gPG cJGH eTJed GdCMcGe bGd ehdGfG MGaX GdOjf CeG HYO adeG cGf Yde Gdabg ef CTQa GdYdhe SjeG ai GdeYGedGJ bGd ehdGfG aNQ GdOjf LeYJ gPg GdeLehYGJ GdBf ef GdcJH GdeJOGhdI s
(3BNQgG (B:s
(3Gbd GdbGVi gPG EPG cGfJ GdJQcI eSJZQbI HGdOjf hEf de jcf faP JUQa GdhGQb ai bUJg ddJeQJGTi JeJ GdcJGH HYhf Gddg Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ CSeGA GdaUhd HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs